The 1990 International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families (ICRMW) - Bojić, Filip (The Universal Protection of Human Rights, 2026)
Abstract: When it comes to the protection of the rights of migrant workers and members of their families, the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families represents an undeniably important international source of law. As one of the main reasons for the adoption of this document, highlighted in the preamble, the importance and extent of the migration phenomenon, which involves millions of people and affects a large number of States in the international community, is stated therein. In this work, the author will point to the long-term struggle that preceded the entry into force of the Convention itself. Although detailed in the regulation of the rights guaranteed to migrant workers and members of their families, it seems that from the point of view of protection for this category of persons, the most important thing is that certain provisions of the Convention apply to migrant workers who do not have a regulated position, as well as to special categories of migrant workers, such as frontier worker, seasonal worker, seafarer, worker on an offshore installation, itinerant worker and project-tied worker. Also, the author will point out a very worrying fact in the paper, which is that this Convention has been ratified by a rather small number of member states of the United Nations Organisation, noting that the United States of America, Canada, Australia, Russia, China, the United Kingdom, as well as no member states of the European Union have done so. Therefore, in the research, this author, along with a detailed analysis of the provisions of the Convention, will pay special attention to discovering the reasons for this insufficient acceptance of the Convention, and will try to find solutions that would lead to its wider acceptance, and to prevent the protection of migrant workers and members of their families from being implemented only de iure, but not de facto.Keywords: migrant workers, members of the family, United Nations Organisation, International Labour Organisation, The International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families, the Committee on the Protection of the Rights of All Migrant Workers and Members of their Families